Recovery of Te for the scrap of Bi2Te3-based alloys by vacuum metallurgy - Dong Kong; Dingya Chen; Zhixiang Kuang; Chenhui Xu; Bo Feng; Xiaoming Hu; Zhuo Chen; Yan Ma; Xi’ an Fan; Guangqiang Li; Yawei Li (Materials Research Express, 2021)
Every year a large amount of scrap can be produced from the Bi _2 Te _3 -based alloys when processing. A clean, new vacuum distillation method is proposed to purify Te from the scrap of Bi _2 Te _3 -based alloys. In this work, the saturated vapor pressure, distillation rate and separation coefficient of each metal element in Bi _2 Te _3 -based alloys are theoretically analyzed. The effects of distillation temperature and time on the volatilization and condensation behavior of elements are studied under the dynamic vacuum of 0.1 Pa. According to the research results, a multi-stage distillation method is proposed, and Te was purified from 41.53% to 98.88% while the total impurity content was reduced to 1.12% through this procedure. Moreover, Te of the scrap of Bi _2 Te _3 -based alloys can be separated and recovered effectively via this three-step vacuum distillation. The results lay the foundation for the industrial purification of Te and provide a low-cost, simple and green recycling process of thermoelectric scrap, which has important practical significance.